History of American Schoolbooks - Carpenter, Charles (University of Pennsylvania Press, 1963)
The lineage of American schoolbooks, like that of our educational system, goes back to Europe and, particularly, to England. The first schoolbooks used in the United States were printed in England and for two hundred years a great influx of books came from sources outside this country. However, with the break from England and the emergence of the United States as a nation, text book publishing came into being in America. This book presents a general portrayal of American textbooks, and along with this, as a requisite accompaniment, a picture of the pioneer-day school system insofar as it had to do with production and early usage of schoolbooks. The author shows how the first textbooks came to be, tells of textbook writers, and traces through the bulk of the material presented the changes that most of the textbook authors brought about. The types of books discussed include the New England primers as well as other types of primers; readers, specially the McGuffey readers; rhetoric and foreign language books; arithmetics; spelling books; literature texts; elocution texts; handwriting and copy books; histories; and many other books that made our school systems what they are today. Besides being a study of the textbook field in America, History of American Schoolbooks is also a history of the United States as reflected in the type of teaching and instructional aids used to educate Americans. A study of this subject is by no means just an interesting side trip into America's past. Many of the books are still influential, and many of the old methods are staging a comeback in the educational field, History of American Schoolbooks should be of interest to educators and historians, as well as teachers, librarians, book collectors, publishers, and general readers who are interested in the evolution and growth of a segment of education and educational publishing that is one of the most important and vital in our country